The Effectiveness of Starfruit (Averrhoa bilimbi L.) As A Hand Sanitizer to Reduce the Bacteria on Hand of Food Handlers - Widiatmo, Tahta Aulianti; Istiqomah, Siti Hani; Mulyaningsih, Tri (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2024)
The cleanliness of the hands of food handlers is a major factor in preventing the spread of disease. The study aims to analyze the effect of using starfruit juice hand sanitizer on the bacteria in the hands of food handlers. The study used a Pretest Posttest with a Control Group Design, conducted in Yogyakarta from March to May 2024. The study involved 24 food handlers. The study used starfruit juice as the basic ingredient for hand sanitizer in three concentration variations (25%, 30%, and 35%). Sampling of hand bacteria was carried out before and after each treatment using the swab method, then incubated for 24 hours at 37°C. Data were analyzed using the Shapiro-Wilk test, One Way ANOVA, and Tukey HSD with a confidence level of 95%. The study results found that starfruit juice hand sanitizer can reduce the number of hand germs (P = 0.001). A concentration of 25% was able to reduce 65.06% (2.29 x 104 to 8.22 x 104 CFU/cm2), a concentration of 30% reduced 69.79% (from 2.09 x 104 to 6.15 x 104 CFU/cm2), and a concentration of 35% reduced up to 85.53% (from 2.72 x 104 to 3.99 x 103 CFU/cm2). The study results also found that more than 85% of respondents liked the color, smell, viscosity, and texture of the hand sanitizer. In addition, the hand sanitizer did not change even though it was stored for up to 28 days (12-140C). Star fruit has the potential to be used as a basic ingredient for making hand sanitizers. In addition to being easy to obtain and cheap, hand sanitizers made from star fruit juice have been proven to be effective as antiseptic.